The role of androgens and polymorphisms in the androgen receptor in the epidemiology of breast cancer - Lillie, Elizabeth O (BioMed Central, 2003)
Testosterone binds to the androgen receptor in target tissue to mediate its effects. Variations in testosterone levels and androgen receptor activity may play a role in the etiology of breast cancer. Here, we review the epidemiologic evidence linking endogenous testosterone to breast cancer risk. Paradoxically, results from observational studies that have examined polymorphisms in the androgen receptor suggest that the low-activity androgen receptor increases breast cancer risk. We review the quality of this evidence and conclude with a discussion of how the androgen receptor and testosterone results coincide.